The identities of insulin signaling pathway are affected by overexpression of Tau and its phosphorylation form - Ma, Ningtian; Liang, Yuyang; Yue, Lingyun; Liu, Pu; Xu, Yuxia; Zhu, Cuiqing (Frontiers in Aging Neuroscience, 2022)
Hyperphosphorylated Tau formed neurofibrillary tangles was one of the major neuropathological hallmarks of Alzheimer’s disease (AD). Dysfunctional insulin signaling in brain is involved in AD. However, the effect of Tau pathology on brain insulin resistance remains unclear. This study explored the effects of overexpressing wild-type Tau (WTau) or Tau with pseudo-phosphorylation at AT8 residues (PTau) on the insulin signaling pathway (ISP). WTau or PTau overexpression in cells exhibited an upregulated basal activity of elements in ISP in general; however, a reduction of ISP signaling transmission responses to insulin simulation showed a relatively higher reaction of IRS-1 phosphorylation at tyrosine 612. Moreover, the detected changes of phosphatase in WTau and PTau cells may be related to ISP dysfunction. In addition, we investigated the effect of the anti-aging drug lonafarnib on the ISP of WTau and PTau cells, which showed that lonafarnib treatment resulted in reduced active levels of ISP elements in PTau cells but not in WTau cells. These differential effects are probably due to Tau phosphorylation modulating lonafarnib-induced alterations in Rhes, as revealed by drug affinity responsive target stability (DARTS) assay. These results provide the linkage of abnormal expression and phosphorylation of Tau to the ISP dysfunction in AD.